2017
DOI: 10.1002/aic.15830
|View full text |Cite
|
Sign up to set email alerts
|

How nano‐scale roughness impacts the flow of grains influenced by capillary cohesion

Abstract: SignificanceWe show that nano-scale changes in surface roughness affect the macro-scale (many-particle) behavior of granular materials influenced by cohesion. Macro-scale effects of roughness are investigated for conditions where cohesion is dominated by either humidity-induced or van der Waals-induced forces. Surface-topography measurements are used to calculate the relevant interparticle cohesive forces. The (force-dominated) macro-scale cohesion measurements are explained via the ratio of the predicted inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…23,24 However, some experiments 5 reported that a liquid bridge may appear when two approaching particles are within a small separation distance before their contact at high liquid loading, and the small-scale particle roughness can initiate an early liquid bridge prior to particle collision. 25 This suggests that a liquid bridge can establish when h is less than a critical value h c . In addition, the experimental study 26 on coordination number of liquid bridge in a static bulk granular system also indicates that each gap between particles might be bridged by liquid as long as it is smaller than the rupture distance (i.e., liquid bridge forms when h < h rup ).…”
Section: Introductionmentioning
confidence: 99%
“…23,24 However, some experiments 5 reported that a liquid bridge may appear when two approaching particles are within a small separation distance before their contact at high liquid loading, and the small-scale particle roughness can initiate an early liquid bridge prior to particle collision. 25 This suggests that a liquid bridge can establish when h is less than a critical value h c . In addition, the experimental study 26 on coordination number of liquid bridge in a static bulk granular system also indicates that each gap between particles might be bridged by liquid as long as it is smaller than the rupture distance (i.e., liquid bridge forms when h < h rup ).…”
Section: Introductionmentioning
confidence: 99%
“…Note that other forms of dimensionless number were also defined in previous works to describe the dynamics of adhesive particles in fluid flow, which is similar to the expression in Equation . Considering that the fluid velocity cannot be directly attained in this work, Equation appears to be most appropriate in the current application, where the pressure gradient and the channel width are both direct input parameters.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, estimates for these quantities were based on complex, rigorous force models for van der Waals forces (Equation ()) and humidity effects (Table 2). Such particle cohesion models can take years to develop and validate, 21,35,42 which leads to two practical questions: (i) what is the minimal, yet sufficient, physics needed in such a model? (ii) Can the corresponding model parameters be extracted from a simple bulk experiment?…”
Section: Discussionmentioning
confidence: 99%
“…(ii) Condensed‐capillary cohesion –The condensed‐capillary cohesive force ( F RH ) is determined by solving the system of equations provided in Table 2, where RH is relative humidity, σ is surface tension, and η RH is the product of ambient air temperature, ideal gas constant and molar density of water; the accuracy and assumptions used for calculating F RH are discussed elsewhere 27,42 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation